ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PENYUSUNAN LAPORAN KEUANGAN PADA USAHA, MIKRO, KECIL DAN MENENGAH (UMKM) DI KOTA PONTIANAK - Putra A, Rico; Setiawan, Aris; Dwi Widyastuti, Reni; Sari, Wilda (Jurnal Akuntansi, Auditing dan Investasi, 2023)
This research is motivated by the ignorance of MSME in Pontianak City about the accounting process anddifficulties in preparing financial reports properly or according to the applicable Financial Accounting Standards(SAK). The different educational levels of MSME actors in Pontianak City affect the knowledge and ability ofMSME actors in preparing financial reports. Some MSME actors in Pontianak City to prepare financial reportswhen needed and most consider that the business being carried out is still not large enough to prepare completefinancial reports. The purpose of doing this research is to analyze the factors of MSME actors in Pontianak Cityin preparing financial statements. The method used is a quantitative research method with a sampling techniqueusing purposive sampling. Data processing and analysis techniques used in this study are validity test, reliabilitytest, classical assumption test and multiple regression test. The results of this study prove that the Socializationvariable has a significant effect on the preparation of financial reports, the MSME Actors' Perception variablehas a significant effect on the preparation of financial reports and Accounting Training has no effect on thepreparation of financial reports.